Use of negative pressure wound therapy over clean, closed surgical incisions - Stannard, James P.; Gabriel, Allen; Lehner, Burkhard (International wound journal, 2012)
The literature has reported that surgical site infections account for 17-22% of health care-associated infections, while surgical wound dehiscence rates range from 0·25% to 3·0% (post laparatomies), 1·6% to 42·3% (post-caesarean incisions) and 0·5% to 2·5% (sternal incisions). These types of incisional complications can become a significant cost burden to the health care system because of lengthy hospital stays and readmissions, additional nursing care and added surgical procedures. Therefore, the type of therapy used for surgical incisions plays a critical role in the healing process. The success of negative pressure wound therapy (NPWT; V.A.C.® Therapy; KCI USA, Inc., San Antonio, TX) for open wounds has been well documented and has led to its use over clean, closed surgical incisions. This review will focus on clinician experience and literature review of incisional NPWT and will include clinical cases describing NPWT's successful use over surgical incisions.
Special Issue: The Impact of Evolving V.A.C® Therapy Technology on Outcomes in Wound Care
Gesehen am 17.08.2018